Highly selective adsorption and efficient recovery of cationic micropollutants from aqueous solution via ultrathin indium vanadate nanoribbons - Feng, Han (2022)
Seeking adsorbents with high adsorption capacity and ease of regeneration is imperative for environmental remediation. Herein, strongly negatively charged two-dimensional (2D) ultrathin InVO4 nanoribbons (NRs) were synthesized. The material exhibited impressive selective adsorption capabilities towards cationic dyes, and the fitted Langmuir maximum adsorption capacity is 789.7 mg/g when using RhB as a model signal pollutant. The adsorption curve towards Rhodamine B (RhB) fits well with the pseudo-second-order (PSO) reaction. The corresponding adsorption isotherm is confirmed in accordance with the Freundlich model, indicating the adsorption is likely a multi-layer adsorption process. Through examining its adsorption activities with positively charged upconversion nanoparticles (UCNPs) and dyes with different surface charges, the strong electrostatic attraction is found to be the predominant adsorption mechanism. Furthermore, the new adsorbents showed remarkable resilience to even large pH variation (from 3 to 12), and could be rapidly and efficiently regenerated using a mixture of water and ethanol (volume ratio 1:1) in 30 min. These advantages are highly favorable for the application of efficient adsorbents for wastewater treatment and resource recovery.